Analysis of Administrative Procedures for Issuing Land Sale and Purchase Letters in Pulau Semikat Village - Ansari, Ansari; Jamaluddin, Yanhar; Warjio, Warjio (Journal La Sociale, 2025)
This study aims to analyze the administrative procedures in the issuance of Land Sale and Purchase Certificate (SKJBT) in Semikat Island Village, Sirapit District, Langkat Regency. Village administration services have an important role in ensuring legal certainty for land purchase and sale transactions, but in its implementation there are still various obstacles. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, direct observations, and documentation. The research informants consist of village officials and the community as service users. The results of the study show that the procedure for issuing SKJBT has followed formal rules, but is still carried out manually without the support of information technology. This has an impact on the slow service process, inefficient document management, and low information transparency. As many as 50% of the community does not know the flow of services and estimated completion time. In addition, limited human resources and lack of socialization are the main obstacles in the implementation of services. Based on Sinambela's public service theory, it was found that services have not fully met the criteria of transparency, efficiency, and accountability. The decrease in the number of SKJBT applications from year to year indicates a decrease in public trust in the village service system. This study recommends increasing the capacity of village apparatus, digitizing administrative procedures, and providing open information as strategic steps to realize effective, responsive, and equitable public services.